A case of typical atrioventricular nodal (AVN) reentrant tachycardia confined to the compact AV node, showing a variety of rare electrophysiological findings, including eccentric AVN echoes. Issue 6 (30th December 2013) - Tanaka, Kazushi; Shiotani, Shinji; Fukuda, Keisuke; Fujihara, Masahiko; Higashimori, Akihiro; Morioka, Nobuyuki; Yokoi, Yoshiaki; Fujimura, Osamu
Abstract: Herein, we report the case of a 49‐year‐old woman with typical atrioventricular nodal (AVN) reentrant tachycardia, confined to the compact atrioventricular node, showing numerous rare electrophysiological findings such as unique AVN reentrant echoes, double ventricular responses, latent retrograde dual AVN pathways, antegrade triple AVN pathways, and longitudinal dissociation within the lower final common pathway.